New statistical developments in data science : SIS 2017, Florence, Italy, June 28-30 /: SIS 2017, Florence, Italy, June 28-30. ([2019]) - Società italiana di statistica., Riunione scientifica, (2017) (Florence, Italy)
No abstract available